The actor-partner interdependence model in the study of aggression and victimization within couples : an empirical examination in 361 dyads - Herrero, Juan; Rodríguez-Franco, Luis; Rejano-Hernández, Lorena; Juarros-Basterretxea, Joel; Rodríguez-Díaz, Francisco J. ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
Studies of intimate partner violence (IPV) have generally focused on only one partner. Although this has allowed advances in scientific knowledge on the causes of IPV, currently recent literature is demanding the need to study both members of the couple. Methodologically, the study of dyads requires the use of appropriate statistical techniques to avoid possible systematic biases (for example, type I error due to dependence of observations). We used the Actor-Partner Interdependence Model to study aggression and victimization in 361 heterosexual couples of young adults. The results indicated, on the one hand, that self-reported mutual aggression was found in more than 50% of the couples. On the other hand, we found that participants victimization was largely predicted by their own aggressive behavior towards the other member of the couple. While this result suggests the existence of a victim-offender overlap, it may also hide an upwards victimization scores bias: when participants are aggressive toward their partners, they may bias their victimization scores upwards to justify their levels of aggression ("I was aggressive because I felt victimized".
Descripción basada en Psychosocial Intervention, vol. 29, núm. 3 (september 2020), P. 165-174.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Sesgo de autoinforme; Agresión mutua; Discrepancia agresión- victimización.; Modelo de interdependencia actor-pareja.; Violencia de pareja; Artículos.